Prior knowledge about Susteinable Development Goals of future teachers - Guardeño Juan, Mireia; Calatayud Requena, Laura; García-Tort, Enrique; García-Rubio, Juan (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of the research is to find out the degree of prior knowledge about the SDGs and the 2030 Agenda of the students in initial teacher training for the Degrees of Teacher in Primary Education, Teacher in Early Childhood Education and Master in Secondary Education of the University of Valencia. Within the framework of a Teaching Innovation project, an inventory of prior knowledge was administered to the participants. Finally, the results were analysed and compared with the aim of improving future interventions on sustainability and curricular innovation.